2013
DOI: 10.1093/geronb/gbt079
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Widowhood Mortality

Abstract: Widowhood's harmful association with mortality show how strongly social support and individual's health and mortality are related. These findings support the larger literature on the importance of social support for health and longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…We find evidence for the notion that health and well-being erodes only for those who disaffiliate, which has an interesting corollary with respect to other forms of social support, particularly spousal support. Most studies of marital status and health compare divorced and widowed individuals to the continuously married, showing that both types of spousal loss are associated with lasting declines in health, which are often attributed to reductions in social support (Sullivan and Fenelon, 2014). However, in more recent years divorced and widowed individuals often report poorer health than those who never marry (Liu and Umberson, 2008), indicating that there is something unique about the loss of social support that reduces health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find evidence for the notion that health and well-being erodes only for those who disaffiliate, which has an interesting corollary with respect to other forms of social support, particularly spousal support. Most studies of marital status and health compare divorced and widowed individuals to the continuously married, showing that both types of spousal loss are associated with lasting declines in health, which are often attributed to reductions in social support (Sullivan and Fenelon, 2014). However, in more recent years divorced and widowed individuals often report poorer health than those who never marry (Liu and Umberson, 2008), indicating that there is something unique about the loss of social support that reduces health.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it is the loss of a source of support that is related to health and well-being rather than simply its presence or absence. This may occur because those who lose a source of social or financial support may have a more difficult time generating suitable substitutes (Sullivan and Fenelon, 2014), while those who simply never had that source of support were able to adapt to its absence with alternative sources of support. Viewed from the perspective of loss, we might expect those who lose the benefits of religious involvement to experience poorer health and well-being than both those who are raised and remain either affiliated or unaffiliated.…”
Section: Introductionmentioning
confidence: 99%
“…A study from the Unites States found education and wealth to protect against mortality in widowhood. However, the authors refer to studies which hold that in higher socioeconomic marriages individuals are more susceptible to grief from losing a spouse or it is more difficult for the surviving spouse to complete the roles performed by the decedent spouse (Sullivan and Fenelon, 2014). In Norwegian data, the effect of socio-economy is expected to be limited as differences in such status are small and the health care system is founded on universal access.…”
Section: Discussionmentioning
confidence: 99%
“…31 This may be because men are less likely than women to have social networks and struggle more to adapt to the loss of help with tasks at home. 32 While the increase in risk of death was not as great for patients with HF that survived their spouse, they still experienced a 44% increased risk of death after their spouse died, demonstrating that the widowhood effect also impacts patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the increase mortality associated with bereavement may not be a direct result of new or worsening physical disease, 33 though adverse psychological responses associated with acute grief 34 and cumulative “wear and tear” associated with caregiving of a dying spouse are likely contributing factors. 32 Further work is needed to delineate the pathways by which widowhood impacts health and outcomes. Recognition of this phenomenon would grant us an important opportunity to intervene with enhanced bereavement care and skill building to promote positive coping and independent functioning in the absence of a spouse.…”
Section: Discussionmentioning
confidence: 99%